International assessment of health care financing : lessons for developing countries - Dunlop, David W. ed. (World Bank WashingtonUS, 1995)
Examines the important role of health insurance at this time in developing countries. Focuses on the macroeconomic context in which health financing takes place in developing countries, the growth of the health sector as development progresses, and the linkages between health financing, health status and indicators of development. Looks at health financing and the use of health insurance in a set of six countries.